On uniqueness of equilibrium in the Kyle Model - Mc Lennan, Andrew (2014)
A longstanding unresolved question is whether the one-period Kyle Model of an informed trader and a noisily informed market maker has an equilibrium that is different from the closed-form solution derived by Kyle (1985). This note advances what is known about this open problem.